"A Body Like a Baby": Social Self-Care among Older People with Chronic HIV in Mombasa. Issue 4 (19th May 2017) - de Klerk, Josien; Moyer, Eileen
ABSTRACT: As part of the chronic disease paradigm now widely used for HIV in sub-Saharan Africa, antiretroviral treatment programs emphasize self-care. In the informal settlements of Mombasa, Kenya, the management of stress—associated with economic precariousness—plays a significant role in self-care practices and ideologies. Based on ethnographic fieldwork, we examine how local narratives of stress and self-care intertwine with social responsibilities of older HIV-positive people. For older Mombassans, living with 'chronic' HIV means living with an unpredictable body, which affects how they are able to care for their kin. The physical reality of living with HIV thus shapes relational networks, making self-care a social practice. While, for some self-care entails managing the body so that its needs are hidden from loved ones, a kind of 'protective secrecy, ' others enlist the support of their children and grandchildren in managing their body, and in that process subtly redefine generational expectations and responsibilities. Abstract :